Validitas dan Reliabilitas Kuesioner Eudaimonic Well-Being Versi Bahasa Indonesia - Kadek Putri Lestari Wardani (Jurnal Siti Rufaidah, 2025)
This study examines the psychometric properties of the Indonesian version of the Questionnaire for Eudaimonic Well-Being (QEWB) with a focus on internal structural validity and reliability. The research aims to provide empirical evidence regarding the feasibility of QEWB as an instrument to assess eudaimonic well-being within the Indonesian population. The process involved the adaptation of the original scale, followed by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to evaluate its dimensional structure. Findings indicate that the Indonesian QEWB demonstrates adequate internal structural validity and reliable measurement consistency. The four-factor model meaning in life, self-discovery, personal expression enjoyment, and personal satisfaction and fulfillment showed the best fit, confirming the stability of this structure across analyses. Further examination through group comparison suggests that the instrument does not exhibit gender bias within the sample, supporting its fairness and applicability across male and female respondents. These results highlight the potential use of the Indonesian QEWB for research and psychological assessment, particularly in studies focusing on well-being, personal development, and organizational contexts. However, the generalization of findings should be approached with caution due to sample limitations. Future research is recommended to involve more diverse populations and explore additional psychometric evidence to strengthen the scale’s applicability across broader cultural and demographic groups.